Activity of domain walls of epitaxial ferrite-garnet films caused by external electric fields - Koronovskyy, V.E.; Vakyla, Y.A. (Functional Materials, 2015)
Sensitivity of domain walls of epitaxial films of ferrite garnets to applying of external constant and variable electric fields under two different experimental conditions was investigated with use of optical polarimetry method. It is shown that "activity" of domain walls increases in the vicinity of areas with non-uniform induced magnetic anisotropy caused by external spatially non-uniform electric field.